A case of restless legs syndrome after BNT162b2 mRNA COVID‐19 vaccination. Issue 3 (26th March 2022) - Ito, Hisashi; Kuroki, Takahiro; Horiuchi, Shigeto; Shinya, Yuichi
Abstract: Restless legs syndrome (RLS) can be secondary to several disorders. We present an 87‐year‐old woman who developed RLS 2 days after the first injection of BNT162b2 mRNA coronavirus disease 2019 vaccine. The symptoms of RLS tended to improve and eventually resolved with the administration of gabapentin.